Four long-acting analgesic hydrazone derivatives of opiates which bind more firmly with opiate receptors - Li Ling-yuan; Ye Cai-ying; Zhang Zhi-rong; Wang Ling; Jin Yin-chang (Acta Pharmacologica Sinica, 2016)
Like morpine(Mor), the reaction of naloxazone(NZO) with opiate receptors was found to be reversible. Rat brain ( without cerebellum) P2 membrane preparation was incubated with NZO( 5 microM) for 15 min and washed 4 times and tested for[3H]etorphine([3H]Etor) binding, the reactivities of both high and low affinity binding sites of opiate receptor were restored. Similar results was obtained with Mor(0.1 mM). The N-methyl analog of NZO especially those with double bond at 7-8,eg ,14-hydroxymorphazone(HMZ) bound more firmly to opiate receptors. But even in the case of HMZ, the binding reactivity of the pretreated P2 preparation could be recovered entirely after 10 washes. The effect of hydrazone derivatives on the longitudinal muscle of guinea pig ileum(GPI) was readily abolished by 3-6 washes and was easily reversed by naloxone(Nx), showing the reversibility of this effect. The N-methylanalogs are agonists. Their analgesic action lasted twice as long as that of Mor and their toxicity was quite low, with no death after icv injection of 180 nmol/mouse. They may be promising long-acting analgesics.